Investigation of the Cyclic Performance of Flat Steel Shear Walls Stiffened with Double-Sided Trapezoidal Corrugated Plates - Chunyang Wu (Journal of Applied Science and Engineering, 2025)
SSWs have been utilized to create and reinforce several structures over the past decades. With the development of steel shear walls (SSWs), corrugated plates have been introduced as a suitable alternative to flat steel plates due to their higher buckling resistance and lateral stiffness. This investigation examines the lateral behavior of FSSW (FSSW) reinforced with a double trapezoidal corrugated plate as a new approach under cyclic loading using finite element software ABAQUS. Double corrugated plates with relative lengths of 0.36 and 0.59 and 2 steel materials of A35 and A572 in three different thicknesses were used. The findings demonstrated that in the examined region, the reinforcement caused the FSSW’s resistance to increase by 18.4% to 49.6%. Also, energy absorption has increased by a minimum of 52% and a maximum of 108%. This exploration also showed that the FSSW without stiffener experienced severe pinching in the hysteresis curve. However, the addition of stiffening double corrugated plates has improved the hysteresis curve and significantly reduced the pinching phenomenon. The equivalent viscous damping of the FSSW sample is 33.21%, while this value varies between 36.72% and 41.5% for stiffened SSWs.